Pemilu Berintegritas Menuju Demokrasi Yang Sehat - Firman Amir (Jurnal Ilmiah Wahana Pendidikan, 2023)
Democracy wants the ruling government to be actually elected by the people, so that this power is actually a service to carry out the people's mandate, to then carry out the aspirations and prosper the people. "Elections with integrity are the key to a Healthy Democracy." if elections are really carried out as well as possible from various aspects, then it will definitely have a positive impact on the development of democracy in Indonesia. Democracy is a means to an end, and the goal to be achieved from democracy is a just and prosperous society. This means that the leaders who are elected in the contestation of democracy must really act to uphold justice, both legal, economic and political justice